2002
DOI: 10.3318/bioe.2002.102.2.81
|View full text |Cite
|
Sign up to set email alerts
|

The use of Members of the Family Chydoridae (Anomopoda, Branchiopoda) as an Indicator of Lake Ecological Quality in Ireland

Abstract: We sampled chydorids (Branchiopoda, Anomopoda) from 29 Irish lakes between June 1996 and July 1997 in order to assess the usefulness of this group as an indicator of lake ecological quality, as required by the recently published EU Water Framework Directive. The lakes represented a wide range of the physicochemical conditions found in Irish lakes. We identified 31 species of Chydoridae from the lakes and used multivariate analysis to elucidate the relationship between the chydorids and their environment. Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
(68 reference statements)
0
6
0
5
Order By: Relevance
“…Every kind of disturbance (e.g., increased pollution, afforestation, or land reclamation) in the neighborhood of the ponds can result in a change of zooplankton composition, abundance, and biomass (Jones, 1986). However, C. sphericus of high tolerance adapted to the colonization of disturbed and even temporary habitats (Mezquita and Miracle, 1997;Eyto and Irvine, 2001;Eyto et al, 2002) and environmental factors. In ponds situated within the forest, the size of C. sphaericus was smaller.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every kind of disturbance (e.g., increased pollution, afforestation, or land reclamation) in the neighborhood of the ponds can result in a change of zooplankton composition, abundance, and biomass (Jones, 1986). However, C. sphericus of high tolerance adapted to the colonization of disturbed and even temporary habitats (Mezquita and Miracle, 1997;Eyto and Irvine, 2001;Eyto et al, 2002) and environmental factors. In ponds situated within the forest, the size of C. sphaericus was smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Small water bodies are often diverse in respect to their origin and morphometry, which can in turn create a wide range of environmental conditions including differences in water chemistry (Williams et al, 2003). However, C. sphericus of high tolerance adapted to the colonization of disturbed and even temporary habitats (Mezquita and Miracle, 1997;Eyto and Irvine, 2001;Eyto et al, 2002) and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The remains of diatoms (Bacillariophyceae) preserved in sediments have been widely used as biological indicators of water quality (Stoermer & Smol, 1999;Battarbee et al, 2001), an approach that utilises robust relationships between diatom species and parameters such as pH (Battarbee, 1984;Jones et al, 1986;Anderson & Korsman, 1990) and TP (Hall & Smol, 1992;Bennion et al, 1996). Several species of Cladocera that preserve well and reflect the nutrient status and pH of lake water (Irvine et al, 2000;de Eyto et al, 2002) have been used in the reconstruction of aquatic conditions (Frey, 1960;Parise & Riva, 1982): Daphniidae and Bosminidae tend to be planktonic, while the Chydoridae are mainly benthic/littoral. Pollen and spores are commonly used in studies of recent environmental changes (Bennett & Willis, 2001) and here are used to estimate changing terrestrial plant cover (e.g., Edwards & Whittington, 2001).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Sparber (2012) reports a decline in water clarity in Feeagh, and hence the depth of the euphotic zone. Additionally de Eyto et al (2002) found a relatively depauperate cladoceran assemblage in comparison to other upland oligotrophic lakes. It is, therefore, possible that reduced water transparency and macrophyte cover could account for the decrease in the abundance of benthic cladocera reported here.…”
Section: Catchment-based Drivers Of Aquatic Changementioning
confidence: 99%